Meaningless Descriptors Increase Price Judgments and Decrease Quality Judgments. Issue 2 (26th January 2021) - Baskin, Ernest; Liu, Peggy J.
Abstract : Consumers commonly encounter products with descriptors. Descriptors with meanings understood by consumers clearly affect judgments of the described products. However, can descriptors for which consumers do not know the word's semantic meaning (as is increasingly common in a globalized world) still affect judgments in systematic ways, via altering the product's perceived prototypicality? We examine two kinds of judgments that typically move in the same direction, but which we propose are affected by prototypicality in opposite directions: (a) judgments of how expensive the product is and (b) expectations of the subjective quality of the product. Four experiments show that meaningless descriptors lead consumers to assume that a product is a less prototypical version in its category, increasing price judgments but decreasing quality expectations. Altogether, meaningless descriptors lead to more negative attitudes toward products. This research thus sheds light on the impact of encountering descriptor words with unknown meaning, showing that encountering such words does not lead to the typical effects wherein factors that lift price judgments also lift quality expectations.